KONSTRUKSI PEMBERITAAN PARTAI DEMOKRAT DI MEDIA MASSA (Analisis Framing Pernyataan Pakar Komunikasi Politik di Kompas.com) - Sodikin, Ali (Kopertais Wilayah I DKI Jakarta dan Banten, 2018)
This research background on the news - reporting kompas.com of the Democratic Party. In the news, media kompas.com citing political communications expert Dr. Heri Budianto. The purpose of this study was to determine the Democrats construction news through the statement of political communications expert Dr. Heri Budianto in Mass Media Kompas.com. Basic theory in this research is the theory of social construction of reality consists of externalization, objectivation, and internalization by Berger and Luckman. Sociological theory of media by Shoemaker and Reese also be the basis of the theory in this study. The method used is framing analysis Entman models with indicators Define Problems, Causes Diagnose, Make Moral Judgment, and Treatment Recommendation. Subject / object in this study are statements of political communications expert Dr. Heri Budiantor published in the online media Kompas.com on the Democratic Party. These results indicate that by using framing approach Entman models can be seen that the statements Political Communication Specialists Dr. Heri Budianto contained in the online media Kompas.com framed in such a way with the selection of issues and highlighting the issue of political reality these parties.